Efektivitas Pembelajaran Secara Daring dengan Menggunakan Aplikasi Google Classroom terhadap Hasil Belajar - Ali Ramatni; Marlina Andriani; Capt. Dafid Ginting; Novita Amri; Muwafiqus Shobri (Departement of Mathematics Education, 2023)
Based on observations of online learning at one of the universities in Sungai Full City, the online learning process is very different from the offline or face-to-face learning process, such as the way of delivering material and how to assess it. It is also of course that there are many obstacles experienced by educators and students during the online learning process. This study aims to see whether online learning using the Google Classroom application on learning outcomes is effective or not. Based on the results of research and hypothesis testing that has been discussed, it can be concluded that the data analysis used is a hypothesis test, where the hypothesis test is used to see the effectiveness of online learning using the Google Classroom application on learning outcomes. In this study hypothesis testing used a one-sample t-test. Based on the results of the study, the table t value < 0.05 = 0.000 < 0.05 so that it can be said H_1 accepted, it can be concluded that online learning using the Google Classroom application on learning outcomes is classified as effective.